Differential sensory and clinical phenotypes of patients with chronic widespread and regional musculoskeletal pain - Finnern, Marina; Kleinböhl, Dieter; Flor, Herta; Benrath, Justus; Hölzl, Rupert (Pain, 2021)
The differentiation of chronic primary pain syndromes into those with widespread vs regional musculoskeletal pain has been characterized by controversial discussions about common or distinct mechanisms and core clinical and sensory criteria. For example, the recent revision of fibromyalgia criteria has discarded sensory characteristics such as number of “tender points.” This study examined empirical evidence related to this diagnostic shift and aimed to identify basic sensory-clinical pain phenotypes in patients with chronic local primary pain (chronic primary back pain [CBP]) and patients with chronic widespread primary pain (fibromyalgia syndrome). Combined sensory-clinical pain phenotypes of 185 patients with previous CBP and fibromyalgia syndrome diagnoses were derived by a stepwise data reduction through descriptive statistical, correlational, principal components and latent class analyses. Clusters were cross-validated by linear discriminant analysis. Four clusters of patients were identified, requiring 4 pressure pain sensitivity markers (number of sensitive tender and control points, pain intensity, and pressure pain threshold at the trapezius) and 2 clinical pain characteristics (pain regions and present pain intensity). Subsequent discriminant analysis revealed that 3 discriminant functions of pressure sensitivity markers sufficed to differentiate the clusters. These sensory-clinical phenotypes differed also in somatic symptoms and impairment but neither in psychopathology nor in psychosocial cofactors. The results highlight the relevance of sensory testing in combination with clinical pain assessment in chronic primary pain syndromes.
Gesehen am 10.06.2021